Vício de consentimento da fiança prestada no contrato de locação sob ótica do tribunal de justiça do estado do Rio Grande do Sul - Signori, Bruna (My University, 2019)
The present work deals with the manifestation of the will of the parties in the provision of the warranty established by the guarantee in the lease, based on the study of the bond originated between the contractors, in order to verify at what moment of the relationship can occur some of the species of vice of will capable of tarnishing the entire contract or at least some of the clauses of the lease. The intention is to demonstrate the importance of the provision of the guarantee in the lease, as well as to highlight the main effects that can arise from the finding of an defect of will in this installment, either in relation to the lease as a whole, or only in relation to the provision of guarantee. The present study concluded that it is extremely difficult to prove that there is a lack of consent in the provision of the guarantee, especially in the lease agreement, since the position of the Court of Justice of Rio Grande do Sul is contrary to the claim of the occurrence of the defect of will in the contract signed by the party that provided the guarantee. In many of the cases examined, the injured party was not even aware that the business in which it was engaged contained any flaws, which meant that sufficient evidence was not produced to substantiate its allegations subsequently to the Court, and the guarantor had to bear with the obligations assumed, even if these were due to some defect of will.(sic)
O presente trabalho trata sobre a manifestação de vontade das partes na prestação da garantia estabelecida pela fiança no contrato de locação, tomando por base o estudo do vínculo originado entre os contratantes, a fim de verificar em que momento da relação pode ocorrer alguma das espécies de vício de vontade capaz de macular todo o contrato ou, pelo menos, algumas das cláusulas da locação. A intenção é a de demonstrar a importância da prestação da fiança no contrato locatício, bem como ressaltar os principais efeitos que podem surgir a partir da constatação de um vício de vontade nessa prestação, seja em relação ao contrato de locação como um todo, ou apenas no que se refere à prestação da fiança. Dentro da ótica analisada, a presente pesquisa concluiu ser de extrema dificuldade a comprovação do vício de consentimento na prestação da fiança, principalmente no contrato de locação, tendo em vista que o posicionamento do Tribunal de Justiça do Rio Grande do Sul é contrário à alegação da ocorrência do defeito de vontade no negócio pela parte que prestou fiança. Ocorre que, em muitos dos casos analisados, a parte prejudicada sequer tinha conhecimento de que o negócio que estava realizando continha algum vício, o que fazia com que não fossem produzidas provas suficientes para comprovar suas alegações posteriormente no Tribunal, tendo a parte fiadora que arcar com as obrigações assumidas, mesmo que estas fossem decorrentes de algum defeito de vontade.(sic)
Keywords: Contratos; Aval e fianças; Direito